Medical and surgical outcome of retropharyngeal abscess and its prognosis - Alwagdani, Ashwag M.; Alwabel, Saga K.; Alyami, Batool H.; Rajkhan, Abdullah A.; Alshehri, Abdulaziz A.; Aloufi, Mohammed S.; Alandijani, Hamza A.; Alsaeedi, Bassam R.; Alshaikh, Roqia M.; Aldhammen, Abrar A.; Alnemer, Rashed A. (International Journal Of Community Medicine And Public Health, 2021)
Although retropharyngeal abscess is not a common condition, it can impact the quality of life of the affected patients, and can even be life-threatening. Asphyxia, upper respiratory tract obstruction, and respiratory distress might then develop secondary to this abscess which continues to grow even larger increasing the seriousness of the complications. Surgical incisions and long-course medical and antibiotic therapies have been described in the literature for the management of retropharyngeal abscess. In this study, the literature review discusses the surgical and medical treatment of retropharyngeal abscesses and the predicted prognosis of the disease after treatment based on evidence obtained from studies in the literature. Early presentation and management are important in achieving better outcomes and enhancing the prognosis. Therefore, patients should be aware enough of the symptoms that might suggest the presence of a retropharyngeal abscess. Using intravenous antibiotics can achieve favorable outcomes. However, some adverse events might be associated and the treatment might not be completed as a result of reduced patient compliance. Surgical management is also efficacious and can be done by different approaches as discussed earlier. Nevertheless, it can also be associated with some complications. Therefore, providing optimal care for these patients should be considered in all scenarios to enhance the prognosis.